2010
DOI: 10.1016/j.jep.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Qualea parviflora Mart.: An integrative study to validate the gastroprotective, antidiarrheal, antihemorragic and mutagenic action

Abstract: methanolic extract from Qualea parviflora had gastroprotective effect related to the increase of gastric mucosa defensive factors such PGE(2) levels and maintain the basal gastric glutathione levels. The methanolic extract also showed anti-Helicobacter pylori activity, anti-hemorrhagic effect and antioxidant action, but absence of analgesic, mutagenic and toxic effects, a profile that adds safety to its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
1
27
0
3
Order By: Relevance
“…Additionally, the gastroprotective effects stopped acting on gastric mucosa (only 60% vs. 98%) when the animals had been pretreated with a sulphydryl (SH) inhibitor. These results support the hypothesis that the activity observed in Q. parviflora is directly related to its capacity of complexing with the gastric mucosal barrier, probably caused by phenolic compounds like flavonoids and ellagic acid derivatives (Mazzolin et al 2010).…”
Section: Antiulcer Activitysupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, the gastroprotective effects stopped acting on gastric mucosa (only 60% vs. 98%) when the animals had been pretreated with a sulphydryl (SH) inhibitor. These results support the hypothesis that the activity observed in Q. parviflora is directly related to its capacity of complexing with the gastric mucosal barrier, probably caused by phenolic compounds like flavonoids and ellagic acid derivatives (Mazzolin et al 2010).…”
Section: Antiulcer Activitysupporting
confidence: 87%
“…The evaluation of diarrheal activity induced by castor oil showed that the crude ethanol bark extract of Q. parviflora significantly (P \ 0.01) diminished 75 4,2 0 ,4 0 -tribenzyloxy-6 0 -trihydroxy-chalcone Fruits Vochysia guianensis Baudouin et al (1983) 7-benzyloxy-4 0 -hydroxy-5-methoxy-flavane Synthesis Vochysia guianensis Baudouin et al (1983) diarrhea by 66%, in relation to the control group (30%) and the standard control loperamide (93%) (Mazzolin et al 2010). …”
Section: Anti-diarrheal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a lack of information to describe any true potential. [6][7][8] The biological activity of medicinal plants from all over the world has been studied by several groups of researchers. These studies are based on the popular uses of different species, 9 as well as on popular knowledge and scientific studies describing medical plant use, with a focus on how these plants could benefit the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several plants provide health benefits by exhibiting antihemorrhagic (Mazzolin et al, 2010), antioxidant (Souza et al, 2012), and antimutagenic activities (Vilar et al, 2009b). Moreover, several studies have demonstrated that numerous active compounds from Brazilian Cerrado plants show promising biological properties for cancer therapy (de Mesquita et al, 2009).…”
Section: Introductionmentioning
confidence: 99%